THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND LEVERAGE ON FINANCIAL DISTRESS IN GENERAL INSURANCE COMPANIES DURING THE COVID-19 PANDEMIC - Mihelle Mihelle; Hendro Lukman (Graduate Program of Universitas Tarumanagara, 2024)
During the COVID-19 pandemic, it was an extraordinary event that occurred unexpectedly and unanticipated by all countries. Easy transmission through saliva droplets has caused many countries to implement community lockdown policies. This condition causes a decline in economic activity coupled with a lot of public spending on health. Many companies have reduced their activities and even closed their businesses temporarily or permanently. This condition has an impact on reducing premium income from general insurance companies. This research aims to analyze the effect of profitability, liquidity and leverage on financial distress in general insurance companies listed on the Indonesia Stock Exchange (BEI) during the COVID-19 pandemic. This research uses 24 data from 8 general insurance companies selected using a non-purposive sampling method. This research uses multiple regression analysis. The results of this research show that profitability and liquidity have a positive effect on financial distress during the COVID-19 pandemic. Meanwhile, leverage shows that it has no effect on financial distress. This research provides a positive signal for investors who want to invest in general insurance companies. The implications of this research provide a signal that companies must manage the use of profits to maintain adequate liquidity, and by carefully managing debt, companies can avoid financial distress.